Answer:
Explanation:
Given the function f(x) and g(x):
We need to multiply them. To do this we need to remember the Product of power property, which states:
And the multiplication of signs:
Then:
Adding like terms, we get:
f(x) × g(x)= x^4 - x^3 - 28x^2 + 16x + 192
We have the function f(x) = x^2 − x − 12 and g(x) = x^2 − 16 and we need to find the multiplication of both functions.
f(x) × g(x) = ( x^2 − x − 12)(x^2 − 16) = x^4 - 16x^2 -x^3 + 16x -12x^2 + 192
Simplifying:
6.3m questions
8.4m answers